Liver fibrosis - M. Merve Aydın,; Kamil Can Akçalı, (Turkish Journal of Gastroenterology, 2019)
Liver fibrosis is a wound-healing response generated against an insult to the liver that causes liver injury. It has the potential to progress into cirrhosis, and if not prevented, it may lead to liver cancer and liver failure. The activation of hepatic stellate cells (HSCs) is the central event underlying liver fibrosis. In addition to HSCs, numerous studies have supported the potential contribution of bone marrow-derived cells and myofibroblasts to liver fibrosis. The liver is a heterogeneous organ; thus, molecular and cellular events that underlie liver fibrogenesis are complex. This review aims to focus on major events that occur during liver fibrogenesis. In addition, important antifibrotic therapeutic approaches and experimental liver fibrosis models will be discussed. Cite this article as: Aydın MM, Akçalı KC. Liver fibrosis. Turk J Gastroenterol 2018; 29: 13-20.